Endogenous LINE-1 (Long Interspersed Nuclear Element-1) Reverse Transcriptase Activity in Platelets Controls Translational Events Through RNA–DNA Hybrids. Issue 4 (April 2018) - Schwertz, Hansjörg; Rowley, Jesse W.; Schumann, Gerald G.; Thorack, Ulrike; Campbell, Robert A.; Manne, Bhanu Kanth; Zimmerman, Guy A.; Weyrich, Andrew S.; Rondina, Matthew T.
Abstract : Objective—: One source of endogenous reverse transcriptase (eRT) activity in nucleated cells is the LINE-1/L1 (long interspersed nuclear element-1), a non-LTR retrotransposon that is implicated in the regulation of gene expression. Nevertheless, the presence and function of eRT activity and LINE-1 in human platelets, an anucleate cell, has not previously been determined. Approach and Results—: We demonstrate that human and murine platelets possess robust eRT activity and identify the source as being LINE-1 ribonucleoprotein particles. Inhibition of eRT in vitro in isolated platelets from healthy individuals or in people with HIV treated with RT inhibitors enhanced global protein synthesis and platelet activation. If HIV patients were treated with reverse transcriptase inhibitor, we found that platelets from these patients had increased basal activation. We next discovered that eRT activity in platelets controlled the generation of RNA–DNA hybrids, which serve as translational repressors. Inhibition of platelet eRT lifted this RNA–DNA hybrid-induced translational block and was sufficient to increase protein expression of target RNAs identified by RNA–DNA hybrid immunoprecipitation. Conclusions—: Thus, we provide the first evidence that platelets possess L1-encoded eRT activity. We also demonstrate that platelet eRT activity regulates platelet hyperreactivity and thrombosis and controls RNA–DNA hybrid formation and identify that RNA–DNA hybrids function as a novel translational control mechanism in human platelets. Abstract : Supplemental Digital Content is available in the text.